The family that cooks together : 85 Zakarian family recipes from our table to yours - Zakarian, Madeline; Zakarian, Anna; Zakarian, Geoffrey (Little, Brown and Company, Hachette Book Group, 2020)
"Meet Anna and Madeline, daughters of Chopped's Geoffrey Zakarian and terrific cooks in their own right! Here they present the definitive cooking guide for kids who want to create joy in the kitchen and the family table! You don't have to be a foodie to love good food, and you definitely don't need to be an adult to make great meals! Anna and Madeline Zakarian have grown up in busy kitchens, and by now they know what's pretty tasty...and what's totally delectable! In their cookbook for kids, Anna and Madeline present flavorful, easy-to-make meals and snacks for cooks of all abilities. Everything from savory breakfasts to scrumptious desserts--and all the nibbles in between--are included, along with simple instructions, limited ingredients, and handy tips and tricks for budding chefs. Mouthwatering photographs of every recipe show you how each dish will turn out, as well as snapshots of the girls' fun- and food-filled days with their family!"--